若a大于0 b大于0 c大于0且a+b+c=1求证(1+a)(1+b)(1+c)大于 8(1-a...
发布网友
发布时间:2024-10-02 21:01
我来回答
共1个回答
热心网友
时间:2024-10-19 13:39
证明:1/a-1
=
(1-a)/a
=
(b+c)/a.
所以原式等于(b+c)/a*(c+a)/b*(a+b)/c
=(b+c)(c+a)(a+b)/(abc).
分子展开,原式
=(a2b+ab2+b2c+bc2+c2a+ca2+2abc)/(abc).
=(a2b+ab2+b2c+bc2+c2a+ca2)/(abc)+2
对a2b+ab2+b2c+bc2+c2a+ca2运用算术-几何平均值不等式,得
a2b+ab2+b2c+bc2+c2a+ca2>=6*(6次根号下(a2b*ab2*b2c*bc2*c2a*ca2))
=6abc.
即原式>=6+2=8.证毕。
热心网友
时间:2024-10-19 13:38
证明:1/a-1
=
(1-a)/a
=
(b+c)/a.
所以原式等于(b+c)/a*(c+a)/b*(a+b)/c
=(b+c)(c+a)(a+b)/(abc).
分子展开,原式
=(a2b+ab2+b2c+bc2+c2a+ca2+2abc)/(abc).
=(a2b+ab2+b2c+bc2+c2a+ca2)/(abc)+2
对a2b+ab2+b2c+bc2+c2a+ca2运用算术-几何平均值不等式,得
a2b+ab2+b2c+bc2+c2a+ca2>=6*(6次根号下(a2b*ab2*b2c*bc2*c2a*ca2))
=6abc.
即原式>=6+2=8.证毕。